Chronic limb ischemia manifestation in COVID-19 infection: awareness and treatment in primary care - Laksono, Sidhi; Siregar, Reynaldo Halomoan; Kusharsamita, Hillary (Faculty of Medicine, Universitas Trisakti, 2021)
Chronic limb ischemia (CLI) is a type of peripheral arterial disease (PAD) that is still underdiagnosed and undertreated despite the increasing incidence, thus becoming a global health burden. And CLI reflects the local manifestations of a lethal systemic disease — atherosclerosis. If left untreated, chronic limb ischemia can result in major limb loss. In this pandemic era, limb ischemia has become one of several clinical manifestations that occur in patients with COVID-19 infection. Systemic inflammation in COVID-19 infection, direct viral infection, hypercoagulable state, and hyperinflammatory response are responsible for damage to the arterial system, causing endothelial dysfunction. Diagnosing PAD has become a challenge especially in the early stage and in the asymptomatic phase. The untreated condition could lead to the development of CLI. The primary physicians in the primary health facilities hold an important role in the early diagnosis and management of patients with CLI symptoms or with risk factors of CLI, especially in patients who have experienced COVID-19 infection. Due to the limitation of diagnostic testing modalities at primary health facilities, the physician can assess the ankle-brachial index (ABI) to determine the presence of CLI. Management of the disease is different for every patient and is customized based on the other comorbidities. Risk factors should be controlled in order to achieve a better outcome. A good management strategy will improve the quality of life of the patient. This review will discuss the occurrence of CLI in COVID-19 infection.